2020
DOI: 10.18865/ed.30.s1.203
|View full text |Cite
|
Sign up to set email alerts
|

Developing a “Tailor-Made” Precision Lifestyle Medicine Intervention for Weight Control among Middle-aged Latino Men

Abstract: Objective: To identify what is important to middle-aged Latino men and their personal goals and values as foundations for a future precision lifestyle medicine intervention that is rooted in Self-Determination Theory.Design: We used a phenomenological, thematic approach to analyze data from 20 semi-structured, individual interviews with Latino men aged 35-60 years.Setting: Community-based settings between November 2017 and May 2018 in South Florida.Participants: Latino or Hispanic men who were aged 35-60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, sociocultural characteristics may contribute to the strong intervention effect found among men. Recent research has shown that Latino males living in the United States seek to embody familism values 49 . Men in this study reported higher familism than women; thus, it is plausible that they had a more favorable response to the incorporation of familism values in our intervention.…”
Section: Discussionmentioning
confidence: 70%
“…However, sociocultural characteristics may contribute to the strong intervention effect found among men. Recent research has shown that Latino males living in the United States seek to embody familism values 49 . Men in this study reported higher familism than women; thus, it is plausible that they had a more favorable response to the incorporation of familism values in our intervention.…”
Section: Discussionmentioning
confidence: 70%
“…This article presents the findings from interview data with Latino men that were collected as part of the formative work of a larger study to inform the development of tailored messages to use in a weight-loss intervention for middle-aged African American men in Tennessee and Latino men in South Florida ( Griffith et al, 2020 ). Based on the literature, the larger study was designed with the understanding that the gender ideals that African American and Latino men were qualitatively different, and thus the messages to motivate men to engage in healthier behavior may be more effective if they sought to capture and reflect their cultural differences.…”
Section: Methodsmentioning
confidence: 99%